Observation of four-top-quark production in the multilepton final state with the ATLAS detector - Aad, G; Åkesson, Torsten ; 0000-0003-4141-5408; Doglioni, Caterina; Ekman, Alexander ; 0000-0002-7032-2799; Hedberg, Vincent; Herde, Hannah ; 0000-0001-8926-6734; Konya, Balazs; Lytken, Else ; 0000-0002-8141-3995; Pöttgen, Ruth ; 0000-0002-3304-0987; Simpson, Nathan Daniel; Smirnova, Oxana ; 0000-0003-2517-531X; Zwalinski, L. (European Physical Journal C. Particles and Fields, 2023)
This paper presents the observation of four-top-quark (tt¯ tt¯) production in proton-proton collisions at the LHC. The analysis is performed using an integrated luminosity of 140 fb - 1 at a centre-of-mass energy of 13 TeV collected using the ATLAS detector. Events containing two leptons with the same electric charge or at least three leptons (electrons or muons) are selected. Event kinematics are used to separate signal from background through a multivariate discriminant, and dedicated control regions are used to constrain the dominant backgrounds. The observed (expected) significance of the measured tt¯ tt¯ signal with respect to the standard model (SM) background-only hypothesis is 6.1 (4.3) standard deviations. The tt¯ tt¯ production cross section is measured to be 22.5-5.5+6.6 fb, consistent with the SM prediction of 12.0 ± 2.4 fb within 1.8 standard deviations. Data are also used to set limits on the three-top-quark production cross section, being an irreducible background not measured previously, and to constrain the top-Higgs Yukawa coupling and effective field theory operator coefficients that affect tt¯ tt¯ production. © 2023, The Author(s).
Keywords: Elementary particles; Statistics; A-center; ATLAS detectors; Final state; Integrated luminosity; Production cross section; Proton proton collisions; Quark production; Standard deviation; The standard model; Top quarks; Tellurium compounds